Higher incidence of perineal community acquired MRSA infections among toddlers - Blumenthal Robert M; Yogev Ram; Kabat William J; Haase Jeffrey; Zhao Xiaochen; Seifried Melissa; McCullough Alexis C; Mukundan Deepa (BMC, 2011)
Abstract Background A six-fold increase in pediatric MRSA infections, prompted us to examine the clinical profile of children with MRSA infections seen at Mercy Children's Hospital, Toledo, Ohio and to characterize the responsible strains. Methods Records were reviewed of pediatric patients who cultured positive for MRSA from June 1 to December 31, 2007. Strain typing by pulsed field gel electrophoresis (PFT) and DiversiLab, SCCmec typing, and PCR-based lukSF-PV gene (encodes Panton-Valentine leukocidin), arginine catabolic mobile element (ACME) and cap5 gene detection was performed. Results Chart review of 63 patients with MRSA infections revealed that 58(92%) were community acquired MRSA (CAMRSA). All CAMRSA were skin and soft tissue infections (SSTI). Twenty five (43%) patients were aged < 3 yrs, 19(33%) aged 4-12 and 14(24%) aged 13-18. Nineteen (76%) of those aged < 3 yrs had higher incidence of perineal infections compared to only 2(11%) of the 4-12 yrs and none of the 13-18 yrs of age. Infections in the extremities were more common in the older youth compared to the youngest children. Overall, there was a significant association between site of the infection and age group (Fisher's Exact p-value < 0.001). All CAMRSA were USA300 PFT, clindamycin susceptible, SCCmec type IVa and lukSF-PV gene positive. Nearly all contained ACME and about 80% were cap5 positive. Of the 58 USA300 strains by PFT, 55(95%) were also identified as USA300 via the automated repetitive sequence-based PCR method from DiversiLab. Conclusions CAMRSA SSTI of the perineum was significantly more common among toddlers and that of the extremities in older children. The infecting strains were all USA300 PFT. Further studies are needed to identify the unique virulence and colonization characteristics of USA300 strains in these infections.